Effect of Diphenhydramine Gargling on Sore Throat in Patients Undergoing Cataract Surgery with Laryngeal Mask Insertion - Mohsen Sabermoghaddam; Elham Bakhtiari; Mohammad Alipour (Reviews in Clinical Medicine, 2020)
Intoduction: Sore throat is a common postoperative complication in patients undergoing general anesthesia. Several factors contribute to this complication, and the airway management method plays a pivotal role in this regard. The present study aimed to assess the effect of diphenhydramine gargling on sore throat in patients undergoing cataract surgery with laryngeal mask insertion. Methods: This placebo-controlled, double-blind, clinical trial was conducted on two groups of intervention and control. The patients in the intervention group gargled 8 cc (20 mg) of diphenhydramine diluted to 20 cc with normal saline 20 minutes before anesthesia induction. The control group patients gargled 20 cc of normal saline 20 minutes before anesthesia induction. The score of sore throat severity was determined based on the visual analogue scale during recovery three, six, 12, and 24 hours postoperatively. Results: Initially, 176 candidates of eye surgery using laryngeal mask airway (LMA) were enrolled in the study, and three patients were excluded from the intervention group due to withdrawal. In the intervention group, 36 patients (42.9%) were female, and 48 patients (57.1%) were male. In the control group, 46 patients (52.3%) were female, and 42 patients (47.7%) were male. The mean age of the subjects was 59.5±16.74 and 57.94±15.74 years in the intervention and controls groups, respectively. No significant differences were observed between the groups in terms of age and gender (P=0.53 and P=0.29, respectively). The mean score of pain severity was 0.3±0.14 and 1.7±0.14 in the intervention and control groups, respectively, which indicated a significant difference between the groups at each measurement point (P<0.001). However, the reported pain severity scores were not correlated with age, gender, mask size, and duration of surgery. Conclusion: Gargling 20 milligrams of diphenhydramine suspension 20 minutes prior to LMA insertion in the patients undergoing eye surgery significantly reduced the post-anesthesia sore throat compared to the control group. Moreover, sore throat had no associations with the age, gender, duration of surgery, and mask size of the patients.